The impact of the Covid-19 pandemic on trauma cases in the orthopedics and traumatology services: A systematic review - Kadek Mercu Narapati Pamungkas; Putu Itta Sandi Lesmana Dewi; I Kadek Wahyu Putra Dyatmika; Made Agus Maharjana; Putu Feryawan Meregawa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
The COVID-19 pandemic has caused all countries to limit their activities to reduce transmission. In the orthopedic and traumatology services, the COVID-19 pandemic has limited the number of non-emergency surgeries, rescheduling activities, limiting hospitalization, etc. This study aimed to quantify the change in the number of visits, trauma cases, surgeries, and telemedicine in orthopedic and traumatology services. The search was carried out on the PubMed, Research Gate, MedRxiv, Elsevier, Link Springer, and Medline databases. The inclusion criteria of the articles used were observational studies. The assessment of the articles’ validity was carried out using a checklist made by the Joanna Briggs Institute. The data being synthesized is limited to quantitative data only. From the 19 articles meeting inclusion criteria, it was found that there was a decrease in the number of visits by 22.4%-86.1%. In additions, there is a decrease in the number of trauma cases by 21.1%-91.2%, lower limb trauma by 20%-77.7 %, upper limb trauma by 6%-78.8%, surgeries by 21.7%-88.8%, elective surgeries by 50%-100%, a change in the number of trauma cases and hip fractures, and an increase in the number of telemedicine application by 9.28%-21.87% in COVID-19 pandemic periode (2020) compared to the pre-COVID-19 pandemic periode (2019 or less). The COVID-19 pandemics affecting the orthopedic and traumatology services decreased the number of visits, especially trauma cases, and surgical intervention